تقييم فعالية الأشعة فوق البنفسجية- ب ضيقة الحزمة في علاج البهاق - الخير, عبد اللله (Latakia University Journal -Medical Sciences Series, 2018)
BACKGROUND: Vitiligo is an acquired depigmentation disorder of great cosmetic importance, affecting 0.5-2% of the general population. Photochemotherapy is the most commonly used treatment modality in vitiligo, but is associated with many short- and long-term side-effects. Recently, narrow-band ultraviolet B (NBUVB) therapy has been reported to be an effective and safe therapeutic option in patients with vitiligo. We studied the efficacy and safety of NBUVB therapy in patients with vitiligo. METHODS: Thirty two patients ( thirteen males and nineteen females), aged 8-56 years, with vitiligo, were treated twice weekly with NBUVB radiation therapy for a maximum period of fifteen weeks. VASI was calculated for every patient every 3 weeks through treatment, and every 4 weeks after the end of treatment. The initial dose was the same for all the patients ; 250mj/cm2 , and increased 20% at each visit until mild erythema lasting <24 hrs reported by patient . RESULTS: At the end of 15 weeks, six each (18.8%) had good or excellent improvement, and three patients (9.4%) had moderate improvement ,and nine patients (28.1%) had poor improvement, and eight patients (25%) had no improvement .the efficacy rate was 46.87% . The response to therapy was better in patients with low ages , low duration of disease, and the low VASI score . Adverse events were limited and transient. CONCLUSION: NBUVB therapy is effective and safe in patients with vitiligo. Long-term follow up is required, however, to establish the stability of repigmentation. البهاق مرض مكتسب , يحدث فيه زوال الاصطباغ و يشكل مشكلة جمالية بالغة الأهمية للمرضى , ويصيب 0.5-2% من مجمل السكان . يعد العلاج الضوئي الكيميائي من أكثر الطرق العلاجية المستخدمة في البهاق و لكنه يترافق مع آثار جانبية طويلة و قصيرة الأمد . مؤخراً اعتبر العلاج بالأشعة فوق البنفسجية –ب ضيقة الحزمة (NB-UVB) خياراً علاجياً فعالاً و آمناً عند مرضى البهاق . كان هدف الدراسة تقييم فعالية و أمان العلاج ب (NB-UVB) عند مرضى البهاق الطرق : ضمت دراستنا 32 مريضاً مصاباً بالبهاق (13 ذكوراً, 19 إناثاً), تراوحت أعمارهم بين ( 8و56) عاماً. تلقوا علاجاً ب(NB-UVB) بمعدل جلستين أسبوعياً و لمدة 15 أسبوعاً . كانت الجرعة البدئية واحدة لكل المرضى وهي 250 mj/cm 2 ازدادت 20% في كل جلسة حتى الوصول إلى حمامى خفيفة .وتمت مراقبة المرضى كل 3 أسابيع أثناء فترة العلاج , وكل 4 أسابيع بعد انتهاء العلاج لمدة 3 أشهر. النتائج: في نهاية الأسبوع 15 من بدء العلاج , ستة مرضى (18.8%) حدث لديهم تحسن ممتاز , ونسبة مماثلة حدث لديها تحسن جيد , و ثلاثة مرضى (9.4%) كان تحسنهم متوسطاً ,و تسعة مرضى (28.1%) كان تحسنهم خفيفاً , و ثمانية مرضى (25%) لم يحدث لديهم أية استجابة . كان معدل فعالية العلاج 46.87% . و النتائج العلاجية أفضل عند من كانت أعمارهم منخفضة و مدة المرض لديهم قليلة وقيمة مشعر VASI منخفضة. الآثار الجانبية كانت محدودة و عابرة . الخلاصة :العلاج الضوئي ب (NB-UVB) علاج فعال و آمن عند مرضى البهاق و يحتاج لمتابعة طويلة الأمد لتقييم استقرار و ثبات عودة التصبغ الحاصلة .